2016
DOI: 10.1186/s12886-016-0269-2
|View full text |Cite
|
Sign up to set email alerts
|

Virtual phacoemulsification surgical simulation using visual guidance and performance parameters as a feasible proficiency assessment tool

Abstract: BackgroundComputer based surgical training is believed to be capable of providing a controlled virtual environment for medical professionals to conduct standardized training or new experimental procedures on virtual human body parts, which are generated and visualised three-dimensionally on a digital display unit. The main objective of this study was to conduct virtual phacoemulsification cataract surgery to compare performance by users with different proficiency on a virtual reality platform equipped with a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…This concept was corroborated by two of our trainees having radial extensions of their CCC when eye movements were introduced. Several studies have shown improved performance of junior ophthalmologists in the operating room after practicing on the Eyesi [12][13][14][15][16][17][18][19][20][21][22]; in particular, the rates of errant CCC are significantly reduced [17, 19,]. One of the limitations of the Eyesi in preparing trainees for real cataract surgery, however, is lack of intraoperative eye movement during the exercises.…”
Section: Discussionmentioning
confidence: 99%
“…This concept was corroborated by two of our trainees having radial extensions of their CCC when eye movements were introduced. Several studies have shown improved performance of junior ophthalmologists in the operating room after practicing on the Eyesi [12][13][14][15][16][17][18][19][20][21][22]; in particular, the rates of errant CCC are significantly reduced [17, 19,]. One of the limitations of the Eyesi in preparing trainees for real cataract surgery, however, is lack of intraoperative eye movement during the exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Most compared computed module performance across first-time operators and found expert/intermediate surgeons to outperform novices. [26][27][28][29][30][31][32][33] Banerjee et al found simulator scores to correlate with prior live surgical performance, 34 while others described similar associations with additional stratification by experience level. 35,36 Meanwhile, Sikder et al endorsed improvement in capsulorhexis scores from baseline after 6 months of residency training.…”
Section: Concurrent and Construct Validity: Simulator Technique And Smentioning
confidence: 95%
“…A potential advantage of simulation training is its ability to correctly identify the relative skill and experience level of the user, which may also be useful in delineating the relative safety of the surgical trainees. 50,51 Four studies 20,35,41,42 in this review looked at transfer of skills to animal tissue from VR alone, with mixed findings. Feudner et al 20 noted an increase in proficiency across several parameters using porcine substitutes, which would indicate the transfer of simulated skills to biological tissue.…”
Section: Predictive Validitymentioning
confidence: 99%